Play4fit: Enhancing users’ engagement with smartphone health and fitness application using gamification concept. - Mohd Kamal, Othman; Nicklos, Ugap; Nur Diyana, Rahman (International Journal of Scientific & Technology Research, 2019)
This paper elaborates the design, development and evaluation of health and fitness smartphone app, Play4fit. The Play4fit app was developed using systematic approach called Mobile application Development lifecycle (MADLC). This study explores the use of gamification concept in engaging the users whilst using the smartphone app. Game experience questionnaire (GEQ) was used to measure participants’ engagement with the Play4Fit app. A study in the wild was conducted with a total of 30 participants and they were assessed using seven components of GEQ, competence, sensory and imaginative immersion, flow, tension, challenge, negative affect and positive effect. Mean scores obtained in this study shows that only two components, competence (M=2.60, SD=0.62), sensory and imaginative immersion (M=2.8, SD=0.71) have the higher mean, above the median value. Results of this study suggest that the gamification app for health ad fitness, Play4Fit have an impact on users’ engagement particularly sensory and imaginative immersion.